Identifikasi Sebaran Peak Ground Acceleration (PGA) Menggunakan Data Mikrotremor di Sekitar Danau Ranau Kabupaten Lampung Barat - Gede Oktiana; Arif Ismul Hadi; Muchammad Farid; Efmadani; Gita Panny Nababan; Sefti Dewi Sari; Yola Dwi Ramadhani (Mataram University, 2026)
West Lampung Regency is located within an active tectonic zone associated with the Sumatra Fault system and is therefore vulnerable to significant earthquake ground shaking. This study aims to identify the spatial distribution of Peak Ground Acceleration (PGA) based on local site characteristics derived from microtremor measurements. Microtremor data were recorded at distributed observation points and analyzed using the HVSR method to determine the dominant frequency (f₀) and amplification factor (A₀) of the soil. The results indicate that f₀ values range from 0.544 to 15.1 Hz, while A₀ values vary between 1.66 and 8.57, reflecting heterogeneous subsurface conditions. These parameters were used to estimate PGA, which ranges from 0.105 to 0.565 g across the study area. Higher PGA values are generally associated with areas characterized by lower dominant frequencies and higher amplification, indicating thicker or softer sediment layers. The resulting PGA distribution map reveals zones with relatively higher seismic response potential. These findings demonstrate the importance of site-specific dynamic characterization in seismic hazard assessment and provide essential information for earthquake risk mitigation and regional development planning in West Lampung Regency.